2014
DOI: 10.1155/2014/732980
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activities against Breast Cancer Cells of Local Justicia gendarussa Crude Extracts

Abstract: Justicia gendarussa methanolic leaf extracts from five different locations in the Southern region of Peninsular Malaysia and two flavonoids, kaempferol and naringenin, were tested for cytotoxic activity. Kaempferol and naringenin were two flavonoids detected in leaf extracts using gas chromatography-flame ionization detection (GC-FID). The results indicated that highest concentrations of kaempferol and naringenin were detected in leaves extracted from Mersing with 1591.80 mg/kg and 444.35 mg/kg, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…According to the datas provided by Zahidah Ayob et.al 21 , the cytotoxicity of Jedarussa vulgaris was analysed by collecting the plant from different locations of Malaysia. Of these, the better results were taken into account for comparison with the present work (Table:3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the datas provided by Zahidah Ayob et.al 21 , the cytotoxicity of Jedarussa vulgaris was analysed by collecting the plant from different locations of Malaysia. Of these, the better results were taken into account for comparison with the present work (Table:3).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, the better results were taken into account for comparison with the present work (Table:3). The standard drug Tamoxifen is used as the positive control by Zahidah Ayob et.al 21 . On comparison, the methanol and ethanol extracts of the plant has the prominent effect against HepG2 cell line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that IC50 naringenin values for BJ and U-118 MG cell lines were equal to 297 and 57 µg/mL respectively. Ayob et al [29] estimated naringenin IC50 values for basal-B mammary carcinoma (MDA-MB-231), basal-A mammary carcinoma (MDA-MB-468) and Chinese hamster ovary (CHO) in similar range of values as 238, 70 and 21 µg/mL after 72 hours treatment using MTT assay.…”
Section: Cytotoxicity Of Naringenin and 8-prenylnaringeninmentioning
confidence: 99%
“…The root and leaves extracts of J. gendarussa have been used traditionally to treat many ailments such as chronic rheumatism, inflammations, bronchitis, headache, arthritis, vaginal discharges, dyspepsia, eye disease and fever (Janarthanam & Sumathi 2010). Leaves and stem extracts of J. gendarussa were reported to possess anticancer, anti-inflammatory, antioxidant, antibacterial, antifungal, antiangiogenis, antiplatelet and hepatoprotective activities (Ayob et al 2014(Ayob et al , 2013Krishna et al 2010aKrishna et al , 2010bPeriyanayagam et al 2009;Sharma et al 2011;Subramanian et al 2012). Phytochemical analysis on leaves of J. gendarussa has showed the presence of flavonoids, alkaloids, amino acids, triterpenoid saponins, aromatics amines, triterpenoid (stigmasterol, lupeol and 16-hydroxylupeol) (Bambang Prajogo et al 2009;Chakravarty et al 1981;Mustafa et al 2010).…”
Section: Introductionmentioning
confidence: 99%